Retinal vessel abnormalities as a possible biomarker of brain volume loss in obese adolescents. (2nd July 2013) - Tirsi, Aziz; Duong, Michelle; Tsui, Wai; Lee, Carol; Convit, Antonio
<x xml:space="preserve">Abstract</x> Objective: Endothelial dysfunction in childhood obesity may precede cerebrovascular damage and cognitive impairment in adulthood. A noninvasive proxy of microvascular health is required to identify the risk for microvascular damage in obese children. Design and Methods The associations of hippocampal volumes and global cerebral atrophy were assessed with retinal vessel caliber in 40 normal BMI controls and 62 obese age‐matched nondiabetic adolescents and the contribution of inflammation, obesity, and insulin resistance to retinal vessel caliber was evaluated. Results Compared to controls, obese adolescents had smaller retinal arterioles (8.3% decrease, P < 0.05) and wider venules (5.4% increase, P < 0.01). Larger retinal arteriole diameters were associated with less global cerebral atrophy (B = −0.24 [95% confidence interval, CI: −0.48, −0.002]) and larger hippocampal volumes (B = 0.01 [95% CI: 0, 0.02]). Venule diameters (B = 84.2 [95% CI: 30.3, 138.1]) were predicted by inflammation (fibrinogen). Arteriolar diameters were predicted by insulin resistance, indicated by logHOMA (homeostatic model assessment, HOMA) values (B = −17.03 [95% CI: −28.25, −5.81)] and body mass index (BMI) (B = −.67 [95% CI: −1.09, −0.24)]. All analyses were adjusted for mean arterial pressure, sleep apnea, and vessel diameter. Conclusions Measures of brain health, BMI, and insulin resistance are associated with retinal vessel caliber. If confirmed in larger studies, retinal arteriolar caliber may serve as a possible noninvasive proxy for brain atrophy in obese adolescents, and the identification of elevated risk for cerebral microvascular disease in adulthood.